Teacher candidates' attitudes towards mistake and instant feedback - Ahmet Yıldız; Hasan Bakırcı; Ali Türkdoğan (Journal of Pedagogical Research, 2023)
This study examines science, mathematics, and classroom teacher candidates' attitudes towards mistake-instant feedback. A total of 531 undergraduate students from different universities in Türkiye participated in the study. Mathematics and science teachers' attitude scale towards mistakes and instant feedback to mistakes (MST-AS) was used to collect data. Data analysis was conducted using descriptive statistics, t-tests, and ANOVA tests. A statistically significant difference between the external and internal attitude dimensions, along with the departments' overall attitude scores, was found. Based on a Tukey's Post Hoc test significant differences were determined between science and mathematics teacher candidates, and between mathematics and classroom teacher candidates in their overall scores, in favour of the science and classroom teacher candidates. The differences among the attitudes of the teacher candidates according to their grade level and achievement was not statistically significant. To better understand the attitudes of teacher candidates, more in-depth or longitudinal studies can be conducted on the variables correlated with high and low attitudes.